Answer:
[tex](-\frac{6}{11}) \times( \frac{3}{4}) = -(\frac{9}{22} )[/tex] in the lowest terms.
Step-by-step explanation:
Here, the given expression is : [tex](-\frac{6}{11}) \times( \frac{3}{4})[/tex]
Solving the given expression, we get:
[tex](-\frac{6}{11}) \times( \frac{3}{4}) = \frac{-6 \times 3}{11 \times 4} =- \frac{18}{44}[/tex]
Now, to express the fraction into lowest terms
18 = 2 x 3 x 3, 44 = 2 x 2 x 11
So, [tex]-\frac{18}{44} = -(\frac{2 \times 3 \times 3}{2 \times 2\times 11} ) = -(\frac{9}{22} )[/tex]
Hence, [tex](-\frac{6}{11}) \times( \frac{3}{4}) = -(\frac{9}{22} )[/tex] in the lowest terms.